SIKAP DAN POLA KONSUMSI SAYURAN RUMAH TANGGA DI KOTA BANDAR LAMPUNG - Tiara, Nabila; Adawiyah, Rabiatul; Kasymir, Eka (Universitas Galuh, 2023)
Vegetables were a type of food that had a complete nutritional content needed by the human body. Consumption patterns made by consumers for a vegetable were inseparable from the various main factors that influence the decision called consumer attitudes. This study aims to analyze attitudes and patterns of consumption of vegetables in households in Bandar Lampung City. Research data was collected on June 2021. Respondents in the study were 60 housewives in Bandar Lampung City. Household consumer attitudes towards vegetables were analyzed using the Fishbein multiattribute model, while descriptive analysis was used to analyze household consumption patterns for vegetables. The results show that household attitudes in Bandar Lampung City towards vegetables have an Ao value of 104.66 and a very positive attitude category. The pattern of vegetable consumption households in Bandar Lampung City includes the average consumption of mustard greens, kale, and spinach of 0.5 kg/week, 0.41 kg/week, and 0.43 kg/week, respectively. The majority of the frequency of consumption of spinach and kale was two times a week, while the consumption of mustard greens was one time a week. The reasons for consumers consuming mustard greens, kale, and spinach were preferences with successive percentages of 43.4 percent, 36.7 percent, and 38.3 percent. Housewives obtain vegetables by buying them directly at traditional markets or modern markets.